Solvent‐Less Synthesis of Compositionally Tuned Mixed Metal (Ni−Zn) Ferrites for Enhanced Electrocatalytic Water Splitting and Supercapacitance - Nyemaga M. Malima; Malik Dilshad Khan; Siphamandla C. Masikane; Felipe M. deSouza; Jonghyun Choi; Ram K. Gupta; Neerish Revaprasadu (ChemElectroChem, 2024)
Abstract Exploring efficient, abundant, economical and stable materials for sustainable energy applications, such as electrochemical water splitting and supercapacitance, is a challenging task. Mixed transition metal spinel ferrites can rationally be customized to attain these features and deliver enhanced electrochemical activity. The catalytic performance of spinels is remarkably influenced by tuning the cationic occupancy at the tetrahedral or octahedral position. Herein, a set of spinel Ni1‐xZnxFe2O4 (0≤x≤1) nanocomposites were obtained via a scalable solventless thermolysis of metal acetylacetonate precursors at relatively mild temperatures. A suite of techniques such as powder p‐XRD, EDX, SEM, TEM, HRTEM, and SAED were employed to confirm the formation of the Ni−Zn ferrite solid solutions. It was found that small amounts of Ni at tetrahedral sites were beneficial for charge storage and hydrogen evolution. For instance, Ni0.2Zn0.8Fe2O4 nanocomposite demonstrated superior HER activity with a much lower overpotential of 87 mV compared to the pristine NiFe2O4 (213 mV) or ZnFe2O4 (164 mV) catalysts. However, Ni‐occupied tetrahedral sites were not suitable for OER, whereby the pristine ZnFe2O4 displayed high catalytic activity with an overpotential of 330 mV, outperforming other electrode compositions. The study helps to identify suitable compositions and site tuning for HER, OER and supercapacitors.